“Cooperative Learning Does Not Work for Me”: Analysis of Its Implementation in Future Physical Education Teachers - Hortigüela-Alcalá, David; Hernando-Garijo, Alejandra; González-Víllora, Sixto; Pastor-Vicedo, Juan Carlos; Baena-Extremera, Antonio (Frontiers in Psychology, 2020)
Cooperative learning (CL) is one of the pedagogical models that has had more application in the area of Physical Education (PE) in recent years, being highly worked in the initial training of teachers. The aim of the study is to check to what extent future PE teachers are able to apply in the classroom the PE training they have received at university, deepening their fears, insecurities and problems when carrying it out. Thirteen future PE teachers (7 girls and 6 boys) aged 20.87±1.43 participated and, after having been trained in CL in various subjects, applied it in the classroom during their internship. A qualitative methodology was used, being the interviews, the teaching diaries and the seminars with the tutor the instruments of data collection used. Three categories of analysis were used: a) initial expectations in the application of the CL; b) problems encountered in its implementation; c) reflection about its application in the future. The results showed how the future teachers did not see their expectations of success fulfilled, encountering resistance from both students and teachers in PE. Furthermore, they reflect the need to continue training in a model that has infinite nuances so that it can be implemented satisfactorily. It is necessary to continue researching a pedagogical model with so many possibilities in the area of PE and with so much transversality on a social level.